Various microbial taxa couple arsenic transformation to nitrogen and carbon cycling in paddy soils - Xin-Di Zhao; Zi-Yu Gao; Jingjing Peng; Konstantinos T. Konstantinidis; Si-Yu Zhang (Microbiome, 2024)
Abstract Background Arsenic (As) metabolism pathways and their coupling to nitrogen (N) and carbon (C) cycling contribute to elemental biogeochemical cycling. However, how whole-microbial communities respond to As stress and which taxa are the predominant As-transforming bacteria or archaea in situ remains unclear. Hence, by constructing and applying ROCker profiles to precisely detect and quantify As oxidation (aioA, arxA) and reduction (arrA, arsC1, arsC2) genes in short-read metagenomic and metatranscriptomic datasets, we investigated the dominant microbial communities involved in arsenite (As(III)) oxidation and arsenate (As(V)) reduction and revealed their potential pathways for coupling As with N and C in situ in rice paddies. Results Five ROCker models were constructed to quantify the abundance and transcriptional activity of short-read sequences encoding As oxidation (aioA and arxA) and reduction (arrA, arsC1, arsC2) genes in paddy soils. Our results revealed that the sub-communities carrying the aioA and arsC2 genes were predominantly responsible for As(III) oxidation and As(V) reduction, respectively. Moreover, a newly identified As(III) oxidation gene, arxA, was detected in genomes assigned to various phyla and showed significantly increased transcriptional activity with increasing soil pH, indicating its important role in As(III) oxidation in alkaline soils. The significant correlation of the transcriptional activities of aioA with the narG and nirK denitrification genes, of arxA with the napA and nirS denitrification genes and of arrA/arsC2 with the pmoA and mcrA genes implied the coupling of As(III) oxidation with denitrification and As(V) reduction with methane oxidation. Various microbial taxa including Burkholderiales, Desulfatiglandales, and Hyphomicrobiales (formerly Rhizobiales) are involved in the coupling of As with N and C metabolism processes. Moreover, these correlated As and N/C genes often co-occur in the same genome and exhibit greater transcriptional activity in paddy soils with As contamination than in those without contamination. Conclusions Our results revealed the comprehensive detection and typing of short-read sequences associated with As oxidation and reduction genes via custom-built ROCker models, and shed light on the various microbial taxa involved in the coupling of As and N and C metabolism in situ in paddy soils. The contribution of the arxA sub-communities to the coupling of As(III) oxidation with nitrate reduction and the arsC sub-communities to the coupling of As(V) reduction with methane oxidation expands our knowledge of the interrelationships among As, N, and C cycling in paddy soils. Video Abstract